2022
DOI: 10.1038/s41598-022-06255-y
|View full text |Cite
|
Sign up to set email alerts
|

Lab-on-chip microscope platform for electro-manipulation of a dense microtubules network

Abstract: Pulsed electric field (PEF) technology is promising for the manipulation of biomolecular components and has potential applications in biomedicine and bionanotechnology. Microtubules, nanoscopic tubular structures self-assembled from protein tubulin, serve as important components in basic cellular processes as well as in engineered biomolecular nanosystems. Recent studies in cell-based models have demonstrated that PEF affects the cytoskeleton, including microtubules. However, the direct effects of PEF on micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Furthermore, suitable chip technology is required that integrates microfluidics for the sample position and manipulation, electrodes system capable of delivering high EF strengths at sufficiently broad frequency bandwidth (required for ns and shorter electric pulses) and compatibility with the advanced microscopy techniques mentioned above. The integrated technology platforms presented, e.g., in [30] , [65] , fulfill all such requirements when coupled to proper imaging techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, suitable chip technology is required that integrates microfluidics for the sample position and manipulation, electrodes system capable of delivering high EF strengths at sufficiently broad frequency bandwidth (required for ns and shorter electric pulses) and compatibility with the advanced microscopy techniques mentioned above. The integrated technology platforms presented, e.g., in [30] , [65] , fulfill all such requirements when coupled to proper imaging techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several experimental [28] , [30] , [31] , [32] and theoretical works [21] , [23] , [33] demonstrating, for example, that an EF can affect the structure of tubulin and microtubules (MTs) [23] and can be used to steer MTs in kinesin gliding assays [11] , little is known about the direct effect of an external EF on kinesin itself. Molecular dynamics simulations, in which EF and mechanical pull were combined, have shown that an intense oscillating EF (up to 10 GHz) affects (mostly decreases) the affinity of kinesin toward tubulin [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%
“…
Fig. 7 ( A ) Total-internal reflectance fluorescence (TIRF) microscopy platform with chip (adapted from [ 155 ]) ( B ) demonstrates the capability of the chip – detachment of antibody-bound microtubules from a surface and their translocation and concentration. ( C , D ) TIRF microscopy images before and after the application of 100× 5 μs, 2.5 MV/m s electric pulses fired at 10 Hz frequency, microtubules are red-labeled fibers.
…”
Section: Electro-manipulation Of Protein Structure and Functionmentioning
confidence: 99%
“…In our opinion, studies of the effect of the electric field on the structure and intermolecular interactions of proteins with other molecules or conductive (or biomimetic) surfaces are interesting research areas. In this review, we demonstrated this on cytoskeletal proteins using chip technologies and computational methods [ 133 , 143 , 155 , 156 , 160 ]. Intense short electrical pulses can modulate the network of non-covalent interactions of proteins and their components and thus interfere with their self-assembly processes, which can be utilized in protein molecular manipulation approaches.…”
Section: Conclusion and Further Prospectsmentioning
confidence: 99%
“…These exciting developments prompt additional investigations, aiming at a deeper elucidation of the mechanistic bases of microtubule dynamics in the hope to further refine and improve the outcome of these clinical applications. As an initiative that may prove rewarding in this direction, very recently, Havelka and coworkers have developed a lab-on-chip microscope platform allowing for the investigation of the effects of microsecond pulsed electric fields (PEF) on microtubule networks of cell-like density [ 45 ]. They found that PEF stimulation resulted in an aggregation of microtubules, overcoming the non-covalent microtubule bonding force to the substrate.…”
Section: An Ensemble Of Physical Energies Acting As the Control Softw...mentioning
confidence: 99%